Energy Dissipation Between Concrete and Composite Waterproof Sheet Interface - Jongsun Park; Byoungil Kim (Buildings)
Underground structures are subject to deterioration conditions in which water leakage occurs through cracks due to the long-term influence of soil and groundwater. Therefore, composite waterproofing sheets can play an important role in securing the leakage stability of structures by combining them with concrete structures. In this study, a total of eight composite waterproofing sheets were used according to the thickness of the compound and the properties of the material attached to the concrete, and the deformation characteristics at the bonding surface were identified through repeated tensile tests. Types A, B, and C, with a compound thickness of 1.35 to 1.85 mm and a single layer, had strong bonding performance, with a deformation rate of 0.5 to 2 × 10−4 and a DE/RE ratio of 0.3 to 1.3; tensile deformation progressed while maintaining integrity with the concrete at the bonding surface. Types D and E were viscoelastic and non-hardening compounds with a compound thickness of 1.35 to 3.5 mm, where the strain rate due to tensile deformation was the lowest, at 0.1 × 10−4 or less, and the DE/RE ratio was −5 to 3; therefore, when internal stress occurs, the high-viscosity compound absorbs it, and the material is judged to have low deformation characteristics. Types F, G, and H, which were 2 to 2.9 mm thick and had two layers using a core material, were found to have characteristics corresponding to tensile deformation, as the strain rate increased continuously from 0.2 to 0.5 × 10−4, and the DE/RE ratio increased up to 8 mm of tensile deformation.